Implikasi Pengaruh Inflasi Dan Suku Bunga Dalam Menentukan Arah Kebijakan Ekonomi Nasional - Ari Nurcahyo Darmawan; Erivina Lucy Kristian (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2024)
This writing has two purposes. First, to describe inflation and interest rates, Second, to analyze the relationship between inflation and interest rates, where both of these are macroeconomic indicators that have an important role in providing decisions and implementing national economic policies. Based on these objectives, the author uses library search methods, searches for relevant sources, and searches for data via the internet. In obtaining the required data and information, the author conducts a literature study first as material for consideration and additional insight and requires reference data as a reference for writing. From the results of the literature conducted by the author, it appears that the inflation variable has a significant effect on interbank money market interest rates.